2018
DOI: 10.1111/1346-8138.14329
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized study of sexual function in men taking dutasteride for the treatment of androgenetic alopecia

Abstract: Treatment with 5α‐reductase inhibitors has been associated with sexual adverse events such as impotence (erectile dysfunction) and decreased libido. The primary objective of this study was to evaluate adverse events related to sexual function, based on their frequency, duration, persistence and associated treatment discontinuations, in men treated with dutasteride for androgenetic alopecia. Participants were randomized to receive double‐blind dutasteride 0.5 mg or placebo once daily for 24 weeks, followed by o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 15 publications
0
16
0
4
Order By: Relevance
“…Dutasteride is approximately three times and 100 times more potent than finasteride for type I and type II, respectively (37). However, ~50% of participants treated with dutasteride for 48 weeks have reported one or more adverse effects, including nasopharyngitis and erectile dysfunction (38,39). Furthermore, studies involving 6,460 patients concluded that dutasteride was effective for improving benign prostate hyperplasia, but was associated with an increased risk of sexual dysfunction (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Dutasteride is approximately three times and 100 times more potent than finasteride for type I and type II, respectively (37). However, ~50% of participants treated with dutasteride for 48 weeks have reported one or more adverse effects, including nasopharyngitis and erectile dysfunction (38,39). Furthermore, studies involving 6,460 patients concluded that dutasteride was effective for improving benign prostate hyperplasia, but was associated with an increased risk of sexual dysfunction (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…All studies had a minimum intervention of 12 weeks of treatment. After a treatment of at least 24 weeks with oral dutasteride, a significant increase in the mean of the hair count was observed in patients receiving oral dutasteride over placebo (MD: 15.92 hairs [95% CI: 9.87–21.96]; p = <0.00001; I 2 = 90%) [16, 17, 20, 21, 23]. Regarding intralesional dutasteride, only 1 study [18] reported the mean change in hair count and therefore a meta-analysis was not possible; however, a statistically significant difference benefiting the intervention was observed in the mean change of hair count when comparing it to placebo (MD: 7.90 hairs [95% CI: 7.14–8.66]; p = <0.00001) (shown in Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…According to the Cochrane RoB 2.0 criteria, 1 study was ranked having a high risk of bias [19] and 3 having some concerns of bias [20][21][22] concerning the randomization process. Subsequently, 3 other studies were ranked as having some concerns of bias [18,19,22] in the deviations from intended intervention domain.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these eight studies, the patients were blinded in four. 76,[79][80][81] The patients in the other four studies were aware of the treatment given.…”
Section: Current Usage Of Health-related Quality Of Life Instruments In Clinical Trials Of Alopeciamentioning
confidence: 99%